Fictions of memory: cultural memory studies and literature - Bojić, Majda (2012)
The intention of this paper is to examine possible relations between the field of studies about memory and literature. As the studies of cultural memory have proven to be an ever growing interdisciplinary field, giving way to discussions about memory and literature, we find it necessary to summarize and problematize the place of literature in cultural memory studies. Another matter of our interest is establishing a dialogue between the field of cultural memory studies and literary studies. In the age of interdisciplinary studies where disciplines are linked and often powered by the same causes, we find it necessary to establish a dialogue between these fields of studies. We find it also important for the investigation of a particular inclusion of literature in the social matters.